STUDI PENEREPAN SYIRKAH PADA BAITUL MAAL WA TAMWIL DI KOTA KENDARI - Muhammad Yusril Ersya Ramadhani; Hasan Aedy; Ernawati Ernawati (JEP (Jurnal Ekonomi Pembangunan), 2019)
This research aims to know what type of contract syirkah used on BMT operational in Kendari, as well as how to apply the terms and syirkah against the principle syirkah principles in Islam at BMT in Kendari. This research was carried out in BMT As-Sunnah and BMT Amanah Kendari. The source of the data on this research stems directly from the research of the informant was 5 (five) people, techniques of data collection carried out in this study i.e. using interviewing techniques and also documentation, other extracted data will be analyzed using qualitative and descriptive-analytical methods. On the basis of the results of the analysis, it can be concluded that BMT As-Sunnah and BMT Amanah Kendari syirkah type of contract apply Al-inaan in operational activities and implementation of the principles and syirkah required on BMT As-Sunnah and BMT Amanah Kendari has appropriated with syirkah al-inaan. Conclusion based on the above, it is advisable to BMT respectively to promote Islamic values in the operation and further strengthen the synergy of BMT colleagues in Kendari.